Factors Influencing Entrepreneurship Decisions in Medan City Students - Windy Septia Triyani; Sri Ramadhani; Nurbaiti Nurbaiti (Institut Agama Islam (IAI) Al-Qolam, 2023)
The purpose of this study was to determine whether there was an influence of at least 1 variable from personality factors, social factors, family environmental factors and educational factors on entrepreneurship decisions in students of North Sumatra University, Medan State University, North Sumatra State Islamic University, North Sumatra Muhammadiyah University and University Medan Ganesha Polytechnic. This research was conducted using 135 respondents. From the results of the study, it was concluded that the most influential variable on the entrepreneurship decisions of Medan city students was social factors. The influence of the next variables sequentially are personality factors, family environment factors and educational factors. The results of this study also show that all variables have a positive and significant influence on the entrepreneurship decisions of Medan city students.